Gastrointestinal symptom burden and dietary intake in patients with chronic kidney disease. Issue 4 (30th April 2021) - Meade, Anthony; Le Leu, Richard; Watson, Nerylee; Jesudason, Shilpa; Clayton, Philip; Faull, Randall; McDonald, Stephen; Trimingham, Claire
Abstract : Background: Gastrointestinal (GI) symptoms can present a significant burden to patients with chronic kidney disease (CKD) but the reported prevalence is inconsistent. Objective: To examine the GI burden and dietary intake in patients with CKD with or without dialysis. Methods: This was a cross‐sectional study of 216 adults, recruited from outpatient and dialysis clinics, with CKD stage 4 or 5 not receiving dialysis (CKD‐ND), or receiving haemodialysis (HD) or peritoneal dialysis (PD). Three questionnaires were administered: the Bristol Stool Form Scale (BSFS); a modified Gastrointestinal Symptom Rating Scale and a short Food Frequency Questionnaire. Outcomes were stool frequency and consistency, GI symptoms and dietary intake. Results: Data were collected from 216 patients (mean age, 63 years [95% CI: 61, 65]; 63% males; CKD‐ND: n  = 134; HD: n  = 67; PD: n  = 15). Mean stool frequency for all groups was one bowel action per day ( p  = .45) and consistency was normal (BSFS type 4, p  = .95). Overall GI symptom burden was low but several symptoms occurred at least "most of the time" including "tiredness/lethargy" (54% of participants), "reduced appetite" (29%), "early satiety" (25%) and "change in taste" (15%). Low intakes of fresh fruit, vegetables, whole‐grains and legumes were found. No associations were observed between diet and GI symptoms. Conclusion: The overall GI symptom burden was low, but >15% of participants reported several symptoms as occurring most to all of the time. Low intakes of fresh fruit, vegetables, whole‐grains and legumes were observed in all CKD patients.